obligation - Garner, Bryan A.; Black, Henry Campbell (Black's law dictionary, 2024)
"Contains over 65,000 legal terms, each clearly and precisely defined in plain English. Fully revised with new material on every page, the 12th edition features over 2,500 new terms"– Publisher's website, viewed on June 11, 2024.